CARCASS YIELD, HAEMATOLOGICAL AND SERUM BIOCHEMICAL PARAMETERS OF BROILER CHICKENS FED DIETARY LEVELS OF PURPLE ORCHID (Piliostigma reticulatum) SEED MEAL - Bah, S. U.; Doma, U. D.; Muhammad, A. S.; Bello, K. M. (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
The study was conducted to evaluate the carcass characteristics, haematology and serum biochemical indices of broiler chickens fed diets containing varying levels of purple orchid (Piliostigma reticulatum) seed meal as substitute to soya bean meal. Three hundred (300) day old chicks (Ross 308) were used for the study that lasted for six (6) weeks. The chicks were assigned to five dietary treatments in a Completely Randomized Design for six weeks. Feed and water were provided ad libitum. All necessary managerial practices were strictly adhered to during the study period. At the end of the trial, four birds per replicate were sampled for carcass and organ measurements, and blood was collected for analysis. The result for Carcass traits differed significantly (P<0.05), with the 20% inclusion level (T3) producing higher live weight, eviscerated, and carcass weights (1850.0, 1319.0 and 1197.67g) comparable to the control (1870.0, 1305.17 and 1243.33g). Dressing percentage and most organ weights were not affected, except gizzard weight (T5, 2.10 to T1, 1.80). Significant (P<0.05) differences occurred in some haematological and serum biochemical indices, but all the values obtained remained within normal physiological ranges of a healthy broiler birds. Incorporating Piliostigman reticulatum seed meal at 20% level improved carcass yield without adverse effects on haematology and serum biochemical parameters.